Annual Prevalence of Use of Potentially Inappropriate Medications for Treatment of Affective Disorders in Parkinson’s Disease - Abraham, Danielle S. (Am J Geriatr Psychiatry, 2020)
OBJECTIVE: To examine the national prevalence of pharmacological treatment of affective disorders in older adults with Parkinson’s disease (PD), and determine the prevalence and risk factors for receipt of an American Geriatrics Society Beers Criteria defined Potentially Inappropriate Medication (PIM) for affective disorder treatment. DESIGN: Cross-sectional analysis of 2014 Medicare data. SETTING: Research Identifiable File data from the Centers for Medicare and Medicaid Services. PARTICIPANTS: Individuals ≥65 years of age with PD whose inpatient, outpatient, and prescription care is administered through the U.S. Medicare Program. MEASUREMENTS: The 2014 prevalence of affective (i.e., depressive and anxiety) disorders was calculated. We assessed prescription fills for affective disorder treatment and classified prescriptions according to PIM status. Patient and clinician factors associated with PIM prescriptions were determined. RESULTS: Of 84,323 beneficiaries with PD, 15.1% had prevalent depression only, 7.5% had anxiety only, and 8.5% had comorbid depression and anxiety. Among those with depression only, 80.7% were treated in 2014 (12.8% of treated received at least one PIM). The annual treatment prevalence was 62.9% (75.9% PIM) and 93.1% (63.9% PIM) in the anxiety only and comorbid group, respectively. In most groups, PIM use was less likely among men and those with dementia; geriatricians were less likely to prescribe PIMs. CONCLUSIONS: Treatment of affective disorders in persons diagnosed with PD is high. PIM use is also common, particularly in persons with anxiety. Future research will quantify the potential effects of these PIMs on clinical and patient outcomes.